2015
DOI: 10.1002/rnj.119
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a 6-Month Nurse-Led Self-Management Program on Comprehensive Pulmonary Rehabilitation for Patients with COPD Receiving Home Oxygen Therapy

Abstract: The findings demonstrate that our program contributes to patients' learning of self-management skills and significantly improves dyspnea, social activity level, walking distance, and overall quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 22 publications
3
12
0
Order By: Relevance
“…The completion rate was 79.3%, which is consistent with previous results [10]- [16]. Most of the dropouts withdrew from the program early because they were too busy or because they had already received education at a hospital, while few patients withdrew during the latter half of the program.…”
Section: Feasibility Of the Programsupporting
confidence: 90%
See 2 more Smart Citations
“…The completion rate was 79.3%, which is consistent with previous results [10]- [16]. Most of the dropouts withdrew from the program early because they were too busy or because they had already received education at a hospital, while few patients withdrew during the latter half of the program.…”
Section: Feasibility Of the Programsupporting
confidence: 90%
“…For this purpose, the "Disease Management" methodology proposed by the Disease Management Association of America seems to be suitable. There have already been several reports about improvement of health outcomes and control of medical expenditure due to implementation of disease management [6]- [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies were conducted in Turkey (Akinci & Olgun, 2011), Australia (Cooke, Moyle, Griffiths, & Shields, 2010;Wood-Baker, Reid, Robinson, & Walters, 2012), Iceland (Ingadottir & Jonsdottir, 2010), China (Liu et al, 2013), Japan (Moriyama, Takeshita, Haruta, Hattori, & Ezenwaka, 2015), Korea (Oh, 2003) In this category, one RCT was identified (Liu et al, 2013) and two studies with a two-group pre-post design (Akinci & Olgun, 2011;Moriyama et al, 2015). These three studies used the SGRQ and included an online video-based breathing programme (Liu et al, 2013), education about COPD and performance of breathing exercises and physical training (Akinci & Olgun, 2011), or a nurse-led self-management educational programme that included an interactive workbook, learning materials and journal for self-monitoring (Moriyama et al, 2015). One study reported a positive effect in favour of the experimental group (MD = 15.6-18.2, p < 0.05) for all of the SGRQ scores (Liu et al, 2013).…”
Section: Nursing Interventions Performed At Homementioning
confidence: 99%
“…This educational program aimed to help patients acquire self-management skills for long-term management of the disease. Our operational definition of self-management education in this study was in line with one from a previous research strategy by Moriyama and colleagues [16]. In this study, we used the self-management education approaches for supporting a process involving patients’ understanding of their disease through the establishment of a partnership between patient and nurse.…”
Section: Introductionmentioning
confidence: 99%